THE PROTECTIVE EFFECT OF SANDOSTATIN IN ACETIC ACID INDUCED EXPERIMENTAL CILITIS IN RATS - Ahmet DOBRUCALI; Mehmet ALTIN; Murat TUNCER; Ersan SANDER; Süha GÖKSEL; Haluk SAVLI; Kadir BAL; Hülya UZUNİSMAİL and İbrahim YURDAKUL and Ergun OKTAY and et al. (Turkish Journal of Gastroenterology, 2020)
-